TERTIARY GEODYNAMICS OF SAKHALIN (NW PACIFIC) FROM ANISOTROPY OF MAGNETIC SUSCEPTIBILITY FABRICS AND PALEOMAGNETIC DATA - Weaver R.; Roberts A.P.; Flecker R.; Macdonald D.I.M. (My University, 2004)
Sakhalin has been affected by several phases of Cretaceous and Tertiary deformation due to the complex interaction of plates in the northwest Pacific region. A detailed understanding of the strain is important because it will provide constraints on plate-scale processes that control the formation and deformation of marginal sedimentary basins. Anisotropy of magnetic susceptibility (AMS) data were obtained from fine-grained mudstones and siltstones from 22 localities in Sakhalin in order to provide information concerning tectonic strain. AMS data reliably record ancient strain tensor orientations before significant deformation of the sediments occurred. Paleomagnetically determined vertical-axis rotations of crustal rocks allow rotation of the fabrics back to their original orientation. Results from southwest Sakhalin indicate a ∼N035°E-directed net tectonic transport from the mid-Paleocene to the early Miocene, which is consistent with the present-day relative motion between the Okhotsk Sea and Eurasian plates. Reconstruction of early-late Miocene AMS fabrics in east Sakhalin indicates a tectonic transport direction of ∼N040°E. In west Sakhalin, the transport direction appears to have remained relatively consistent from the Oligocene to the late Miocene, but it has a different attitude of ∼N080°E. This suggests local deflection of the stress and strain fields, which was probably associated with opening of the northern Tatar Strait. A northward-directed tectonic transport is observed in Miocene sediments in southeast Sakhalin, mid-Eocene sediments in east Sakhalin, and in Late Cretaceous rocks of west and northern Sakhalin, which may be associated with northwestward motion and subduction of the Pacific Plate in the Tertiary period. The boundaries of the separate regions defined by the AMS data are consistent with present-day plate models and, therefore, provide meaningful constraints on the tectonic evolution of Sakhalin.
Keywords: Anisotropy of magnetic susceptibility; Strike-slip; Geodynamics; Sakhalin; Tertiary